3T non-injected phase-contrast MRI sequences for the mapping of the external carotid branches: In vivo radio-anatomical pilot study for feasibility analysis. Issue 1 (January 2018) - Bettoni, Jérémie; Pagé, Gwénaël; Salsac, Anne-Virginie; Constans, Jean-Marc; Testelin, Sylvie; Devauchelle, Bernard; Balédent, Olivier; Dakpé, Stéphanie
Abstract: An essential stage in head and neck microsurgical reconstruction is the choice of recipient vessels. To make relevant choices, surgeons must rely on accurate imaging techniques. The objective of the study was to examine the feasibility of Phase-Contrast sequences to conduct the pre-operative tests without injection and provide precise radio-anatomical data over the entire vessel region. The challenges were the large velocity range, the lack of contrast, and the large spatial resolution needed to image vessels below 5 mm in diameter. Thirty-one healthy volunteers were included in an MRI prospective study. The anatomical and morphometrical characteristics of the collaterals of the external carotid artery were determined associating 3D PCA and 2D Cine MRI-PC sequences (average protocole duration time of 49 min ± 4 min). The average diameter was measured to be 2.1 ± 1.4 mm for the superior thyroid artery, 2.2 ± 1.1 mm for the lingual artery, 2.7 ± 1.6 mm for the facial artery, 2.6 ± 1.4 mm for the internal maxillary artery, and 2 ± 1.4 mm for the superficial temporal artery. With a vessel identification success rate of 98%, the study showed for the first time that Phase Contrast MRI allowed non-invasive and non-operator dependent anatomical analyses of small caliber vessels without the use of agent contrast. It also proved that the designed sequences could be used on patients and provided valuable pre-operative information for head and neck surgery.